An investigation on the need for internal auditing in risk management: a case of James North Zimbabwe (pvt) ltd) - Chinjo, Tracy V. (Midlands State University, 2017)
The aim of this research was to investigate the need for internal auditing in risk management at James North Zimbabwe (Pvt) Ltd. This research was triggered by the fact that the company is experiencing escalating levels of business risks yet the company has no internal audit function. A census of James North Zimbabwe employees was conducted and the researcher collected primary data through interviews and questionnaires. Data was analysed and presented in form of tables, pie charts and graphs. The study revealed that the absence of an internal audit function at JNZ is contributing to the increase in business risks in the company. The study also provided the practices that can improve JNZ’s risk management processes.